Family Needs After Traumatic Brain Injury: A VA TBI Model Systems Study. Issue 6 (9th November 2022) - Finn, Jacob A.; Klocksieben, Farina A.; Smith, Austin N.; Bernstein, John; O'Neil-Pirozzi, Therese M.; Kreutzer, Jeff S.; Sander, Angelle M.; Dreer, Laura E.; Niemeier, Janet P.; Cotner, Bridget A.; Nakase-Richardson, Risa
Abstract : Objective: To describe the self-reported needs of family caregivers of service members and veterans (SMVs) who sustained a traumatic brain injury (TBI) and to identify predictors of the unmet family caregiver needs. Setting: Five Department of Veterans Affairs (VA) Polytrauma Rehabilitation Centers (PRCs). Participants: Family caregivers of SMVs enrolled in the VA PRC TBI Model Systems (TBIMS) national database who were within their first 5 years post-TBI ( n = 427). Design: Observational study. Main Outcome Measure: The Family Needs Questionnaire-Revised (FNQ-R) was completed by each SMV's designated caregiver. Analyses: Descriptive analyses were conducted on the FNQ-R responses at the item, domain, and total score levels. Unadjusted univariable and adjusted multivariable regression models were fitted to identify predictors of total unmet needs and unmet family need domains. Results: FNQ-R item-level and domain-level descriptive results indicated that health information was the most frequently met need domain. In contrast, emotional and instrumental support domains were the least often met. On average, family caregivers reported that 59.2% of the 37 FNQ-R needs were met at the time of the follow-up assessment. Regression models indicated that both the number of SMV-perceived environmental barriers and whether the SMV received mental health treatment within the past year predicted the number of unmet FNQ-R needs. SMV-reported environmental barriers predicted increased unmet needs in all 6 family caregiver domains, and SMV mental health treatment in the past year predicted more unmet family caregiver emotional support, community support, and professional support needs. Conclusions: The current findings can be used to inform policy and programming for VA and Department of Defense to proactively address the specific needs of families and caregivers experienced in the first 5 years post-TBI.